Penegakan Hukum Terhadap tersangka Tindak Pidana Pencurian Kelapa Sawit Di Kabupaten Kotawaringin timur (Studi Kasus Putusan Nomor: 286/Pid.Sus/2025/PN Spt) - Bagus Muhammad Ramadhan; Yoyok Ucuk Suyono; Ernu Widodo (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The increasing number of palm oil theft cases in the jurisdiction of the Kotawaringin Timur Police Resort from January to October 2025 has become the background of this study. This research aims to analyze the law enforcement process against suspects involved in palm oil theft and to identify the factors influencing its implementation based on Decision Number: 286/Pid.Sus/2025/PN Spt. This study employs normative legal research with a case study approach. The analysis is conducted using descriptive qualitative methods based on primary legal materials, including Law Number 1 of 1946 concerning the Indonesian Criminal Code and Law Number 39 of 2014 concerning Plantations, supported by secondary and tertiary legal materials. The results show that law enforcement against palm oil theft suspects in Kotawaringin Timur Regency has been implemented through the application of Article 362 of the Criminal Code and Article 107 letter (d) of Law Number 39 of 2014 concerning Plantations, where the legal elements of the offense have been fulfilled. Several factors influence the effectiveness of law enforcement, including legal regulations, the capacity of law enforcement officers, limitations in facilities and infrastructure, the level of community legal awareness, and cultural perceptions that sometimes consider palm oil harvesting acceptable under customary beliefs.